Analyzing the Mobile Robot Localization Performance in Partially Observable Conditions - Hamzah, Ahmad; Nur Aqilah, Othman; Saifudin, Razali; Mohd Rusllim, Mohamed (2014)
This paper deals with theoretical investigation of robot localization considering partial observability conditions. The problem is very important as most of the mobile robot applications are controllable but not observable due to some aspects. The paper investigate the importance of correlation to the mobile robot estimation through the technique of decorrelating some of the elements of state covariance of the updated state covariance. To demonstrate the effect of correlation, two cases of partial observability are examined which are the unstable and stable partial observability. The cases are build based on the conﬁgurations of the state covariance for mobile robot references when doing observations. Our preliminary results suggest that the system with stable partial observability shows very good and consistent estimation while the unstable case lead to inconsistency and erroneous estimation.